Privatisation as An Educational Sector Reform In India - Kalita, Jagriti (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The privatization of education brings up the issue with regards to what degree the public functions of education are undermined if schools are given to privately owned businesses rather than the state. Market failure involves the hazard that education may never again be given at a palatable level, and that imbalances could increment immensely if just the privileged sections can bear the cost of good education. Others, be that as it may, would contend that a solid state funded educational framework must be a precondition for social equity. Deregulation as privatization and institutional autonomy in educational sector are impetuses for social disparities while centralised education is regarded to inhibit the legacy of educational opportunities over generations. The following paper deals the debate on privatising educational sector of India in great detail.